ANGPTL8 requires ANGPTL3 to inhibit lipoprotein lipase and plasma triglyceride clearance - Haller, Jorge F. (J Lipid Res, 2017)
Angiopoietin-like (ANGPTL)3 and ANGPTL8 are secreted proteins and inhibitors of LPL-mediated plasma triglyceride (TG) clearance. It is unclear how these two ANGPTL proteins interact to regulate LPL activity. ANGPTL3 inhibits LPL activity and increases serum TG independent of ANGPTL8. These effects are reversed with an ANGPTL3 blocking antibody. Here, we show that ANGPTL8, although it possesses a functional inhibitory motif, is inactive by itself and requires ANGPTL3 expression to inhibit LPL and increase plasma TG. Using a mutated form of ANGPTL3 that lacks LPL inhibitory activity, we demonstrate that ANGPTL3 activity is not required for its ability to activate ANGPTL8. Moreover, coexpression of ANGPTL3 and ANGPTL8 leads to a far more efficacious increase in TG in mice than ANGPTL3 alone, suggesting the major inhibitory activity of this complex derives from ANGPTL8. An antibody to the C terminus of ANGPTL8 reversed LPL inhibition by ANGPTL8 in the presence of ANGPTL3. The antibody did not disrupt the ANGPTL8:ANGPTL3 complex, but came in close proximity to the LPL inhibitory motif in the N terminus of ANGPTL8. Collectively, these data show that ANGPTL8 has a functional LPL inhibitory motif, but only inhibits LPL and increases plasma TG levels in mice in the presence of ANGPTL3.